'When I am being rushed it slows down my brain': constructing self-understandings as a mathematics learner. Issue 5 (4th May 2017) - Lambert, Rachel
ABSTRACT: Understanding learning disabilities (LDs) as constructed through multiple cultural practices including discourse, this paper focuses on a Latino middle school student with a LD named Elijah. This study documents both the discourses and practices used to position Elijah as a mathematics learner, as well as his use of similar discourses as he constructs a complex set of self-understandings as a mathematics learner. Elijah is positioned by discourses that prioritise speed as an indicator of mathematical ability, as well as discourses that construct students with LD as having both intelligence and differences such as processing speed. An analysis of interview and observational data suggests that Elijah constructed a unique set of self-understandings as a mathematics learner. Like his sixth-grade special education teacher, Elijah seems to differentiate between knowledge and the performance of knowledge in school. He created a unique identity as both 'fast' and 'slow' in mathematics, rejecting the binary found in many mathematics classrooms. These findings suggest that multiple discourses circulate in schools about ability and disability in mathematics.